The American Crocodile: An Indicator Species for Everglades Restoration - Rebecca G. Harvey; Michiko Squires; Jeff Beauchamp; Frank J. Mazzotti; Laura A. Brandt (EDIS)
The American crocodile (Crocodylus acutus) is a top predator that lives along the southern tip of peninsular Florida, inhabiting saltwater, brackish water, or freshwater near coastal areas in mangrove-lined ponds, creeks, coves, man-made ponds, and canals. This 3-page fact sheet explains how monitoring populations of threatened crocodiles can help scientists chart the success of projects to restore the Everglades. Written by Rebecca G. Harvey, Michiko Squires, Jeff Beauchamp, Frank J. Mazzotti, and Laura A. Brandt, and published by the Department of Wildlife Ecology and Conservation, September 2016.